Interdyscyplinarny charakter kulturoznawczego pojęcia kultury - Walczak, Monika (Człowiek i Społeczeństwo, 2015)
Two tendencies determine the use of the concept of culture within Polish cultural studies: the tendency to understand culture in a generalized, comprehensive way and the tendency to narrow it down, to particularize it. The former tendency is visible, among other things, in the concept of culture adopted by the main founding traditions of Polish cultural studies: the Wrocław tradition established by Stanisław Pietraszko and the Poznań tradition introduced by Jerzy Kmita. The latter tendency is inherent in these conceptions of cultural studies that take as their object different fragments of culture for example contemporary culture, or artistic culture. The problem of interdisciplinarity presented in the paper is asked in the context of the notion of culture specific for cultural studies. The paper investigates, whether and in what sense the concept of culture is interdisciplinary. Do cultural studies researchers employ a specific notion of culture shared by them and suitable therefore to perform the function of integrating cultural studies as the domain of interdisciplinary studies? Which notion of culture – the general or the particular one – can serve the purpose better?